Professionalism in traditional Chinese medicine (TCM) practitioners: a qualitative study - Yu Heng Kwan; Sarah Chooi; Sungwon Yoon; Xiang Ling Ang; Jie Kie Phang; Hwee Ling Koh; Julian Thumboo; Swee Cheng Ng; Warren Fong (BMC, 2020)
Abstract Background Medical professionalism is important for establishing public trust in doctors. Its definition is culture-sensitive. However, no research has explored medical professionalism in Traditional Chinese Medicine (TCM) practitioners. This study aims to (a) establish the domains of professionalism in TCM practitioners in Singapore, and to (b) compare the domains of professionalism of practitioners trained in TCM and practitioners trained in conventional medicine. Methods Data for this qualitative study was collected through in-depth interviews (IDIs) with TCM practitioners. IDIs were audio-recorded and transcribed verbatim. Thematic analysis was conducted by two independent coders using the Professionalism Mini-Evaluation Exercise (P-MEX) as a framework. The domains of professionalism in TCM and conventional medicine were then compared, using data from a similar study on professionalism in practitioners trained in conventional medicine. Results A total of 27 TCM practitioners (40.7% male) participated in this study. The four domains of professionalism in the P-MEX, namely doctor-patient relationship skills, reflective skills, time management and inter-professional relationship skills, and two new sub-domains, "communicated effectively with patient" and "demonstrated understanding and integrated with conventional medicine", were relevant to TCM practitioners. This is largely similar to that of practitioners trained in conventional medicine, with a few differences, including "ensured continuity of care" and "used health resources appropriately". Conclusion The domains of professionalism in TCM practitioners were established and they are similar to that of practitioners trained in conventional medicine. This study is the first to define medical professionalism in TCM practitioners. Findings will provide guidance on the education of professionalism in TCM practitioners.